2005
DOI: 10.1002/chin.200539207
|View full text |Cite
|
Sign up to set email alerts
|

A Virtual Screening Approach for Thymidine Monophosphate Kinase Inhibitors as Antitubercular Agents Based on Docking and Pharmacophore Models.

Abstract: 2005 Computers in chemistry V 0380 A Virtual Screening Approach for Thymidine Monophosphate Kinase Inhibitors as Antitubercular Agents Based on Docking and Pharmacophore Models. -(GOPALAKRISHNAN*, B.; APARNA, V.; JEEVAN, J.; RAVI, M.; DESIRAJU, G. R.; J. Chem. Inf. Model. (J. Chem. Inf. Comput. Sci.) 45 (2005) 4, 1101-1108; Bioinf. Div., Adv. Technol. Cent.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 1 publication
0
18
0
Order By: Relevance
“…Efforts to develop useful chemical probes of Mtb with the potential to inspire novel lead compounds have seen relatively limited application of cheminformatics methods that have been utilized in other therapeutic areas (5,19,31).…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to develop useful chemical probes of Mtb with the potential to inspire novel lead compounds have seen relatively limited application of cheminformatics methods that have been utilized in other therapeutic areas (5,19,31).…”
Section: Discussionmentioning
confidence: 99%
“…Our pharmacophore model displays a superior performance with 76.3% retrieval efficiency when the false-positive tolerance is only 1.0% (see Figure s1 in Supporting Information). The enrichment factor (E) calculated according to Gopalakrishnan et al [39] was found to be 12.2, indicating that it is 12 times more probable to pick an active compound from the database than an inactive one. The validation has shown that our model is capable of being used in virtual screening of large databases.…”
Section: Pharmacophore Model Validationmentioning
confidence: 99%
“…Additionally the 1-eNOS complex is stabilized by a s-bond cooperative chain, heme C OÁ Á ÁHO w H (92H)Á Á ÁO w H (168H)Á Á ÁO C(1). Participation of water molecules in the molecular recognition of ligand within the active site is commonly found in several proteins [31][32][33]. However, in this context, water molecules seem to be critical in masking the active site differences, thereby facilitating the substrate binding in the NOS isoforms.…”
Section: Role Of Water In Substrate Bindingmentioning
confidence: 96%